2023
DOI: 10.1002/anie.202300537
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Synthesis of Triflones Bearing Two Non‐Adjacent Stereogenic Centers

Abstract: Trifluoromethylsulfones (triflones) are useful compounds for synthesis and beyond. Yet, methods to access chiral triflones are scarce. Here, we present a mild and efficient organocatalytic method for the stereoselective synthesis of chiral triflones using α‐aryl vinyl triflones, building blocks previously unexplored in asymmetric synthesis. The peptide‐catalyzed reaction gives rise to a broad range of γ‐triflylaldehydes with two non‐adjacent stereogenic centers in high yields and stereoselectivities. A catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…18 Examples include aldol 19 and conjugate addition reactions with a diverse range of electrophiles, including nitroolefins, 18,20−25 maleimides, 26,27 dicyanoolefins, 28 allenamides, 29 and vinyl triflones. 30 These conventional catalyst development studies were guided by detailed conformational and mechanistic studies that revealed, for example, the importance of a balance between flexibility and rigidity, 7 the trans/cis ratio of the tertiary amide, 18,31 endo-N-pyramidalization of the enamine intermediate, 32,33 and the role of an internal proton donor for the performance of the tripeptide catalysts. 34 Among the many Pro-Pro-Xaa catalysts identified for different reactions, H-DPro-Pro-Glu-NH 2 features a rigid ground state, 7 but all others (e.g., H-Pro-Pro-Asp-NH 2 , H-DPro-Pro-Gln-OH, H-DPro-Pro-Gln-OH) are more flexible.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Examples include aldol 19 and conjugate addition reactions with a diverse range of electrophiles, including nitroolefins, 18,20−25 maleimides, 26,27 dicyanoolefins, 28 allenamides, 29 and vinyl triflones. 30 These conventional catalyst development studies were guided by detailed conformational and mechanistic studies that revealed, for example, the importance of a balance between flexibility and rigidity, 7 the trans/cis ratio of the tertiary amide, 18,31 endo-N-pyramidalization of the enamine intermediate, 32,33 and the role of an internal proton donor for the performance of the tripeptide catalysts. 34 Among the many Pro-Pro-Xaa catalysts identified for different reactions, H-DPro-Pro-Glu-NH 2 features a rigid ground state, 7 but all others (e.g., H-Pro-Pro-Asp-NH 2 , H-DPro-Pro-Gln-OH, H-DPro-Pro-Gln-OH) are more flexible.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These catalysts feature a single well-defined conformation. This excellent match between the mechanism-guided and modeling-guided results is striking. In prior catalyst optimization campaigns that used mechanism-based considerations, distinctly different Pro-Pro-Xaa catalysts emerged. , , These reactions include aldol and conjugate additions to vinyl triflones, maleimides, , or disubstituted nitroolefins. , These “manually” optimized catalysts afford the addition products with high stereoselectivities (typically 90–99% ee) and feature a residue other than Glu in the Xaa position, varied absolute configurations at the α-carbons of the amino acids, alternative coordinating moieties to COOH, substituted Pro residues, or a combination of those features. These expert-knowledge-guided catalyst optimizations built on the common Pro-Pro-Xaa scaffold.…”
Section: Coda: Comparison Of Expert-knowledge- Versus Data-science-gu...mentioning
confidence: 99%
“…Taking inspiration from these elegant studies, we designed a series of 9-fluorenyl-based meso -epoxides as a platform to investigate the feasibility of chiral Brønsted acid catalyzed desymmetrization reactions of both stereoisomers of epoxides (Scheme B, right). Compared to previous studies, , our design offers unique features.…”
mentioning
confidence: 99%
“…More recently, He and Zhang, along with their co-workers, have independently reported on the efficient protocol for enantio- and diastereodivergent synthesis of 1,3-nonadjacent stereocenters bearing both a stereogenic center and a stereogenic axis via the synergistic Cu/Pd dual catalysis (Scheme A, B) . However, all of the aforementioned accomplishments have resulted in chiral molecules bearing stereogenic elements in a mono-1,3-nonadjacent relationship . To our knowledge, the catalytic asymmetric stereodivergent construction of bis-1,3-nonadjacent stereocenters has yet to be realized (Scheme A, C) .…”
mentioning
confidence: 99%
“…Solid-phase peptide synthesis (SPPS) is a widely used method for chemical peptide synthesis. , To monitor the completion of peptide coupling reactions, the Kaiser test based on the ninhydrin reaction has been utilized to visualize unreacted free amino groups on the resin (Figure a) . However, the Kaiser test has several disadvantages: (1) some amino acids, such as proline , and N -alkylated , and α,α-disubstituted , α-amino acids, are not detectable; (2) a small amount of resin must be aliquoted from a peptide synthesis vessel for the test; (3) toxic KCN is necessary as a reductant; (4) quantitative analysis is impractical; etc. Aliquoting resin is a common drawback for reaction-based amine detection methods. , To address these issues, nondestructive one-pot amine detection methods have been developed .…”
mentioning
confidence: 99%